Ifosfamide-loaded poly (lactic-co-glycolic acid) PLGA-dextran polymeric nanoparticles to improve the antitumor efficacy in Osteosarcoma. Issue 1 (December 2015) - Chen, Bin; Yang, Jie-Zuan; Wang, Li-Feng; Zhang, Yi-Jun; Lin, Xiang-Jin
Abstract Background Osteosarcoma is a typical bone cancer that primarily affects adolescents. The therapeutic activity of drugs is limited by their severe drug-related toxicities, therefore, a therapeutic approach which is less toxic and highly effective in tumor is of utmost importance. Method In this study, ifosfamide-loaded poly (lactic-co-glycolic acid) (PLGA)-dextran polymeric nanoparticles (PD/IFS) was developed and studied its anticancer efficacy against multiple osteosarcoma cancer cells. The drug-loaded nanoparticle was characterized for physical and biological characterizations. Results The formulated PD/IFS showed a high drug loading capacity and displayed a pH-sensitive release pattern, with a sustained release profile of the IFS. PD/IFS nanoparticles exhibited remarkable in vitro anticancer activity comparable to that of free IFS solution in a concentration dependent manner in MG63 and Saos-2 cancer cells. PLGA-dextran by itself did not affect cell viability of cancer cells indicating its excellent biocompatibility. The formulation exhibited significantly higher PARP and caspase-3/7 expression in both the cancer cells. Conclusion Our study successfully demonstrated that nanoparticulate encapsulation of antitumor agent will increase the therapeutic efficacy and exhibit a greater induction of apoptosis and cell death.